Structural characterization of human liver heparan sulfate - Preeyanat Vongchan (2018)
The isolation, purification and structural characterization of human liver heparan sulfate are described.1H-NMR spectroscopy demonstrates the purity of this glycosaminoglycan (GAG) and two-dimensional1H-NMR confirmed that it was heparan sulfate. Enzymatic depolymerization of the isolated heparan sulfate, followed by gradient polyacrylamide gel, confirmed its heparin lyase sensitivity. The concentration of resulting unsaturated disaccharides was determined using reverse phase ion-pairing (RPIP) HPLC with post column derivatization and fluorescence detection. The results of this analysis clearly demonstrate that the isolated GAG was heparan sulfate, not heparin. Human liver heparan sulfate was similar to heparin in that it has a reduced content of unsulfated disaccharide and an elevated average sulfation level. The antithrombin-mediated anti-factor Xa activity of human liver heparan sulfate, however, was much lower than porcine intestinal (pharmaceutical) heparin but was comparable to standard porcine intestinal heparan sulfate. Moreover, human liver heparan sulfate shows higher degree of sulfation than heparan sulfate isolated from porcine liver or from the human hepatoma Hep 2G cell line. © 2004 Elsevier B.V. All rights reserved.